Command Strategies in Animated Discourse: A Pragmatic Analysis of Hey Arnold! Episode “Full Moon” - Abdussalam Jabaruddin Yamjirin (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
Animated cartoons transcend mere entertainment, offering a rich linguistic landscape that mirrors real-world interactions. This study investigates the pragmatics of directive speech acts, focusing on command strategies in Hey Arnold!, a series celebrated for its realistic portrayal of childhood social dynamics. The episode "Full Moon" serves as a case study, capturing relatable scenarios of peer influence, authority, and moral dilemmas frequently encountered in communities. Using frameworks from Leech (1983), Brown and Levinson (1987), and Blum-Kulka (1987), commands are categorised into direct, indirect, politeness-enhanced, and justification-driven forms. Results reveal that institutional figures employ bald-on-record commands to assert dominance, while peer interactions favour indirect and mitigated directives. Justification-based strategies emerge as tools for subtle persuasion, reinforcing Blum-Kulka’s claim that rationalisation fosters compliance. This research underscores that animated cartoons are not simplistic; they act as linguistic laboratories reflecting real-world discourse. By decoding how commands function in fictional dialogue, we gain deeper insights into the nuanced mechanics of directive speech act strategies in everyday communication. Hey Arnold! exemplifies how language shapes social hierarchies and power dynamics, offering valuable perspectives on the interplay between speech acts and social behaviour.